Mainstreaming Citizen Engagement through the World Bank Group’s Country Engagement Model - Masud, Harika; Kumagai, Saki; Grandvoinnet, Helene (World Bank, Washington, DC, 2020)
Efforts to mainstream citizen engagement into the Country Partnership Framework (CPF) cycle have the potential to contribute toward achieving country development goals and the World Bank Group’s twin goals of ending extreme poverty and boosting shared prosperity by maximizing the impact of citizen-centric initiatives. Informed by the findings of a desk review of the Systematic Country Diagnostic (SCD) and corresponding CPF from FY14 to FY19, this technical note is intended to serve as a resource for World Bank task teams to elaborate on options and entry points for systematic mainstreaming of citizen engagement in the CPF cycle, specifically in preparing the SCDs, CPFs, Performance and Learning Reviews, and Completion and Learning Reviews.